Self-Regulated Learning as a Strategy to Overcome Sleep Procrastination in Early Adulthood - Nadia; Hanggara Budi Utomo (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2025)
Bedtime procrastination is the habit of delaying sleep time that should be done on time, often due to involvement in other activities such as social media use or social activities. This study aims to develop a Self-Regulated Learning (SRL) based learning module to address bedtime procrastination in early adults, specifically for teachers at SLB River Kids. This module is designed to help individuals manage their sleep habits through an approach that includes clear sleep planning, management of external distractions, and self-reflection. The results of the study show that the SRL module is effective in reducing bedtime procrastination and improving sleep quality among the participants, although there is variation in the application of the suggested techniques. This module is considered a useful tool to assist early adults, especially those who face work and social life challenges that disrupt their sleep patterns.